Implementing ISO 9000 series in maintenance organization / Mohammad Irfan Ahmad Zaki - Ahmad Zaki, Mohammad Irfan (2004)
The objective for any maintenance organization is to complete the job (maintenance work) in the shortest possible time, with the lowest cost and meet the expected standard. It cannot be deny that the maintenance organization will use their best endeavour to meet the first two objectives but let the objective to run its course. However, the three objectives are in effect complementary to one another. To achieve the first two objectives ideally the maintenance organization must implement a quality system that can effectively provide detailed procedures for the process. Most of the problem and difficulties in the achievement of quality in the maintenance organization-can be attributed to the nature of the industry itself. The industries differ from the others. Most building failures are also believe to have resulted from the quality of the design and construction process.